presentatie. - Singer Museum Laren ([Amsterdam] : Nederlandse Kunstkoopersbond, 1976)
Appel, Karel ; Lindstrom, B. ; van Gogh, Vincent ; Christoforou, J. ; Picasso, Pablo ; Bitran, Albert ; Delvaux, Paul ; Mondriaan, Piet ; van Velde, Geer ; de Smet, Gustaaf ; van Doesburg, Theo ; van der Leck, Bart A. ; Huszar, Vilmos ; Montijn, Jan ; Westerik, Co ; Raveel, ROger ; Lataster, Ger ; Bayens, Hans ; van Hall, Maja ; Morandi, Giorgio ; van Dongen, Kees ; etc.
presentatie, Singermuseum Laren, mei 1976
boek